Analisa dan Perancangan Sistem Informasi Kasir pada Maxx Coffee - Shiam, Ahmad Fajri; Syamsianto, Didik; Pramudia, Maha; Ananda, Yesica; Desyani, Teti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Currently, there are many cash register systems that have not yet entered the modern system or are still manual counting. And because of this, it can result in a lot of time wasted for customers who have little time to buy a few items. Not to mention if there is a miscalculation in calculating the total number of all items purchased by the customer, it will be detrimental to both the restaurant and the customer. Therefore, now there is a development where the calculation at the cashier becomes faster and more efficient because of the innovations provided by several people to simplify and expedite the calculation of the total number of items purchased by customers That is now using the automatic count method provided by several restaurants for overall smoothness in transactions between buyers and also the restaurant. For the results, we can feel it now where we don't have to wait long for payment and also we are now easier to pay for our orders because it is added with an online payment system that aims to reduce the amount of paper used in printing money in paper form